Perspectives of clinical nurse educators on competency-based nursing teaching in blended learning environments during nursing internship: A descriptive qualitative study - Zhou, Na; Yang, Lili; Pan, Jiayu; Lv, Kai (Nurse education in practice, 2024)
To investigate the perspectives of clinical nurse educators regarding the challenges and essential elements of teaching competence in blended learning environments during nursing internships to inform the development of a competency-based teaching model. Competency-based teaching and blended learning play important roles in enhancing the learning experience of nursing internship trainees. Internship trainees refer to nursing students undergoing supervised practical training in ‎clinical settings.‎ However, clinical nurse educators frequently encounter challenges in acquiring the necessary competence for successful implementation of blended learning strategies. A descriptive‎ qualitative study. This study used semi-structured interviews with 11 certified nurse educators (CNEs) from diverse clinical disciplines in a tertiary hospital in China. Purposive sampling ensured diversity across key characteristics. Ethical approval was obtained and interviews were digitally recorded, transcribed and analyzed thematically. Theoretical saturation guided data collection, with precise measures taken to ensure confidentiality and anonymity. Thematic analysis, employing a constant comparison technique, systematically identified various themes related to blended teaching competence. This approach provided valuable insights into CNEs' perspectives and practices. The analysis involved theoretical sampling, line-by-line coding and comparative evaluation with supporting text materials. The in-depth analysis of teaching competence among clinical nurse educators in blended learning settings during nurse internships revealed five key themes: professionalism, teaching literacy, subject expertise, information literacy and interpersonal communication. These themes recognized clinical nurse educators’ perspectives towards establishing a competency-based nursing teaching model for a blended learning environment for nurse internships. Moreover, these perspectives are also crucial in enhancing teaching literacy through effective instructional methods, engagement strategies and the promotion of critical thinking skills. Identifying these themes contributes to efforts to improve teaching effectiveness and enhance learning outcomes for internship trainees in a blended learning context.